Analysis of Business Differences in The Tempe Industry in The City of Surakarta - Adi, Raden Kunto; Harisudin, Mohamad; Qonita, Raden Rara Aulia (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4431, 2021)
The purpose of this study was to identify the business performance of the tempe industry and to analyze the tempe industry in Surakarta. The basic method in this research is method explorative. Data retrieval apart from census technique was also carried out through in-depth interviews with several key informants using snow ball technique. The research location was determined purposively. Types of data consist of primary data and secondary data. The method of data analysis used analytical descriptive analysis, explaining and analyzing descriptions of the business performance of the tempe industry. The results showed that most of the sources of capital for tempe-making business come from their own capital. Based on the results of the study, the total cost of one month incurred by tempe craftsmen is Rp. 26,096,657. The average tempe production for one month produces 40,529 tempe. The amount of monthly revenue for the tempe industry is IDR 28,779,571.00 so that the business profit in one month is IDR 2,709,914.00. Suggestions given based on the results of this study are that the producers of the tempe industry increase tempe production, so that higher business profits can be obtained, producers optimize promotions by utilizing social media continuously